Weakening greenhouse gas sink of intermittent river under human activities for the Inner Mongolia grassland region in China - Xinyu Liu; Huifang He; Weijie Han; Wentao Liang; Zhenqi Yang; Jianying Guo (Journal of Hydrology: Regional Studies)
Study region: This study was conducted in the Tabu River Basin, located within the Yinshanbeilu Grassland in central Inner Mongolia Autonomous Region, China. Study focus: The Tabu River's runoff is significantly affected by human activities. This study investigated the spatiotemporal dynamics of the CO2 flux under varying runoff conditions, identified the key drivers of CO2 emissions, and assessed the influence of human activities on these emissions within the watershed. New hydrological insights for the region: Our findings revealed a significant decline in runoff in the Tabu River Basin since 2010, primarily driven by human activities. Following river drying, riverbed ecosystem respiration (ER) increased, whereas riparian wetlands exhibited a marked decrease in ER. Furthermore, net ecosystem exchange (NEE) results indicated a shift from a carbon sink to a carbon source in the riparian wetlands during periods of river drying. Soil moisture content (SMC), above-ground biomass (Bios), and soil bulk density (ρb) emerged as critical factors regulating CO2 emissions. These findings highlight the necessity for continuous, long-term monitoring of intermittent rivers and in-situ greenhouse gas flux measurements under diverse hydrological conditions. To enhance the resilience of riverine ecosystems and sustain their carbon sequestration potential, future management of the Tabu River Basin should focus on optimizing irrigation strategies and adapting reservoir management practices. Such interventions will enable efficient allocation and sustainable utilization of water resources.